Burden of gastrointestinal cancers in Asia, 1990–2019 - Chengwei Xia; Yini Liu; Xin Qing (BMC Gastroenterology)
Abstract Objectives Gastrointestinal (GI) cancers are a major cause of morbidity and mortality worldwide. However, there has been no comprehensive assessment of GI cancers in Asia. Study design This was an epidemiological study. Methods The study calculated the incidence and deaths of six common GI cancers in Asia between 1990 and 2019 using data from the Global Burden of Disease study. The data are presented by sex, age, year, location, and risk factors, and are shown as counts and rates. Results In 2019, the age-standardized incidence rates (ASIR) for colorectal, esophageal, gallbladder and biliary tract (GBTC), liver, pancreatic, and stomach cancers were 23.88, 8.24, 2.77, 7.97, 5.41, and 19.77, respectively. The age-standardized death rates (ASDR) for colorectal, esophageal, GBTC, liver, pancreatic, and stomach cancers were 12.49, 7.73, 2.53, 7.22, 5.47, and 14.67, respectively. From 1990 to 2019, there was an increasing trend in incidence and deaths for esophageal, liver, and stomach cancer, while a decreasing trend was observed in colorectal, GBTC, and pancreatic cancer. The burden of GI cancer increased successively in older generations and was higher in males than in females. Furthermore, this burden varied significantly across Asian subregions and countries. Dietary risks, smoking, alcohol use, and high BMI contribute to GI cancer mortality. Conclusions GI cancers continue to be the primary contributor to the tumor burden in Asia, with increasing absolute numbers but varying age-standardized measures over the past three decades.